Video Game Pursuit (VGPu) Scale Development: Designing and Validating a Scale With Implications for Game-Based Learning and Assessment. (February 2020) - Sanchez, Diana R.; Langer, Markus
Background. Recent research ongame-based assessment andtraining demonstrates growing interest in how individual differences affect game-based outcomes. However, there is still a lack of clarity about the variables that affect important game-based outcomes and issues with measurement approaches regarding these variables (e.g., no validation of scales). This study develops a model wherevideo game pursuit (VGPu) is measured as an antecedent to entering the gaming cycle . We propose that VGPu-related antecedents lead to a feedback loop where engaging in the game cycle affects game-related outcomes which again affect the antecedents of re-entering the game cycle . Moreover, wevalidate a measure of VGPu and provide construct as well as criterion validity evidence. Methods. Within three studies ( N = 716) we develop and validate theVGPu scale - a psychometrically sound measure of intentions to pursue video games. Using Amazon's MTurk (Studies 1, 2), participants responded to theVGPu items and we conducted exploratory and confirmatory factor analyses showing thatVGPu consists of a general latentVGPu factor with four subfactors (Intentional Game Play, Generalized Game Self-Efficacy, Enjoyment of Games, Prone to Game Immersion). In Study 3, students responded to theVGPu items, to items examining construct validity, and played three video games from different genres to assess criterion-related validity of game performance and game reactions. Results. Results demonstrate construct and criterion-related validity showing thatVGPu correlates with other game-related scales and predicts game performance and game reactions. Discussion. The findings demonstrate the value of theVGPu scale for research and practice becausepursuing video games seems to be an important variable for predicting how individuals perform and react to game-based activities. Finally, we discuss implications for future research and practice in the realm ofgame-based assessment andtraining .